The Marseille mosaic a Mediterranean city at the crossroads of cultures - Ingram, Mark 1957-; Kleppinger, Kathryn ca. 20./21. Jh (Space and place, 2023)
"Formerly the gateway to the French empire, the city of Marseille exemplifies a postcolonial Europe reshaped by immigrants, refugees, and repatriates. The Marseille Mosaic seeks to address the city's past and present, exploring the relationship between Marseille and the rest of France, Europe, and the Mediterranean. Proposing new models for the study of place by integrating approaches from the humanities and social sciences, this volume offers an idiosyncratic "mosaic," which vividly details the challenges facing other French and European cities and the ways residents are developing alternative perspectives and charting new urban futures"--